Chinese L1- Croatian L2- Difficulties and Success - Tomić, Diana (Array, 2011)
This pilot study presents the results of speech training exercises (phonetic correction) in 5 (4F and 1M) Chinese students of Croatian. The effects of training were assessed through listening evaluation tests and acoustic analysis of vowels. Twenty students of phonetics, native speakers of Croatian evaluated the pronunciation skills of Chinese students. The acoustic analysis of vowel formants in terms of F1 and F2 frequency was performed for female speakers only and compared to native speaker values. Both methods revealed some improvement in the quality of pronunciation in general, and provided guidelines for further course of phonetic speech training for Chinese students.